Math 222 - Selected Homework Solutions from Sections 2.2 and 2.3 Instructor - Al Boggess Fall 1998 Page 98 - Section 2.2 5 We are to show det(A) = n det A. The key is to write A = (I )A Now take determinants: det(A) = det(IA) = det(I ) det A Now, I has n factors of down the diagonal and so det(I ) = n . Thus det(A) = n det A, as desired. 6 Suppose A is a nonsingular matrix (so A,1 exists). We are to show det(A,1 ) = det1 A The key equation is I = A,1 A Taking determinants, we get 1 = det(AA,1 ) = (det A)(det A,1 ) Solving, we get as desired. 1 = det(A,1 ) det A 1 9 If A and B are row equivalent by row operations of type I (switch rows) and of type III (add a multiple of one row to another), then the determinants of A and B dier only by a minus sign, at most. This is because, type III operations do not change the determinant at all and type I operations change the sign. If only type III operations are involved, then det A = det B . 11 We assume that A = LU where L is lower triangular (with ones on the diagonal) and U is upper triangular (with diagonal elements u11; u22 ; u33 . Clearly, det L = 1 and det U = u11 u22u33 . Therefore det A = det L det U = u11 u22 u33 . 12 We are to prove that AB is nonsingular if and only if A and B are nonsingular. We rst assume that A and B are nonsingular and then prove that AB is nonsingular. The key equation is det(AB ) = det A det B If A and B are nonsingular, then det A and det B are nonzero. So the product, det A det B is nonzero and hence det(AB ) 6= 0. Thus AB is nonsingular. Now assume that AB is nonsingular and we will show that both A and B are nonsingular. Again we use the equation det(AB ) = det A det B If AB is nonsingular, then det(AB ) is not zero. This implies that BOTH det A and det B are nonzero. Thus both A and B are nonsingular, as desired. Page 104 - Section 2.3 8 We are to show The key equation is det(adjA) = (det A)n,1 A,1 = det1 A adjA Using problem 5 on page 98 with = det1 A and problem 6, we get 1 = det A,1 = 1 det(adjA) det A (det A)n 2 Solving for det(adjA) we get det(adjA) = (det A)n,1 as desired. 12 We are to show that if det A = 1, then adj(adjA) = A. The key equation is A,1 = det1 A adjA If det A = 1, then adjA = A,1 or A = (adjA),1 . Now apply ** with A replaced by adjA. We obtain 1 adj(adjA) (adjA),1 = det(adj A) Now as already mentioned, the left side is A. On the right side, since adjA = A,1 , we have det(adjA) = det(A,1 ) = 1= det A = 1. Therefore from the previous equation A = adj(adjA) as desired. 3